0394 Efficacy of Cognitive Behavioral Therapy for Insomnia on Post-Menopausal Quality of Life. (27th April 2018) - Arnedt, J T; Cheng, P; Fellman-Couture, C; Tallent, G; Kalmbach, D; Singh, M; Roth, T; Drake, C L
Abstract: Introduction: Insomnia occurs in more than 50% of post-menopausal women, is among the most distressing and debilitating symptoms, and adversely affects quality of life. In a randomized controlled trial, we compared the efficacy of multi-component Cognitive Behavioral Therapy for Insomnia (CBT-I) to a behavioral only insomnia therapy (Sleep Restriction Therapy, SRT) and to a Sleep Education control (SE) for improving quality of life symptoms at post-treatment and 6-month follow-up. Methods: Post-menopausal women (n=117, mean age 56.4 + 5.2 years, 44.4% African American) meeting Research Diagnostic Criteria for insomnia that was temporally associated with menopause were recruited. Participants underwent two nights of PSG to screen for other sleep disorders and to verify an average wake after sleep onset of > 45 minutes. Eligible participants were randomized to one of three treatment conditions: 6-session CBT-I (n=38), 2-session SRT (n=36), or 6-session SE (n=43). Participants completed the Menopause-Specific Quality of Life (MENQOL) questionnaire before and after treatment and at 6-month follow-up. Results: Linear mixed models showed an overall Condition by Time interaction for the Physical subscale of the MENQOL (F=3.3, p<.01) and Time effects for the other three subscales (Vasomotor, Psychosocial, and Sexual, ps<.05). For CBT-I, post-treatment scores improved on the Physical (p<.002), Vasomotor (p<002), and Psychosocial (p<.05) subscales but not the Sexual subscale. At 6-month follow-up, scores on these subscales remained improved relative to baseline (Physical p<.001, Vasomotor p<.001, Psychosocial p<.007) and not different from post-treatment. In contrast, no pre-to post-treatment differences in subscale scores were found for the SRT or SE conditions, and only the Vasomotor subscale (p<.001) was lower at 6-month follow-up compared to baseline in the SE condition. Conclusion: Compared to SRT and SE, only multi-component CBT-I improved multiple quality of life domains at post-treatment in post-menopausal women with insomnia. These improvements were sustained at 6-month follow-up. Support (If Any): R01 NR013959 (CL Drake).